2002
DOI: 10.1046/j.1526-4637.2002.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Long-term Failures of Lumbar Spine Surgery

Abstract: We were able to establish a predominant diagnosis in 94% of our patients. Foraminal stenosis remains the leading cause of FBSS, but painful discs are also common. Recurrent disc herniation is seen less often than in the past, and there is increased recognition of neuropathic pain. Knowledge of the potential causes of FBSS leads to a more efficient and cost-effective evaluation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(112 citation statements)
references
References 9 publications
3
98
0
11
Order By: Relevance
“…In our series it did not overwhelm the results of these studies [12,53]. Moreover, the complication rates reported by Waguespack and Ebeling were higher and could be explained by different referral patterns and categories provided.…”
Section: Discussionsupporting
confidence: 55%
“…In our series it did not overwhelm the results of these studies [12,53]. Moreover, the complication rates reported by Waguespack and Ebeling were higher and could be explained by different referral patterns and categories provided.…”
Section: Discussionsupporting
confidence: 55%
“…It is not a definitive diagnosis and it is considered a syndrome because it has many explanatory etiologies as clinical as surgical [1][2][3][4][5] . The main factor is to delineate its cause through the evaluation of clinical history, physical examination and psycho-partner-economic profile, since the treatment is specific and individualized.…”
Section: Resumo -Objetivomentioning
confidence: 99%
“…In the epidemiologic studies revised, the main causes are foraminal stenosis, internal disc disruption, pseudarthrosis and neuropathic pain, which together, correspond more than 70% [1][2][3][4] . A practical method is divide the patients into those with predominance of lumbar pain versus predominance of leg pain, this allows to establish a logical sequence that will be used to carry the complementary examinations.…”
Section: Resumo -Objetivomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some patients continue to complain of persistent or new low back pain after surgery. Cases of recurrent low back pain and/or lower extremity pain after lumbar/lumbosacral surgery are referred to as failed back surgery syndrome [5][6][7][8][9][10][11]. Several authors have suggested that the sacroiliac joint (SIJ) may be a possible source of persistent pain [4,12,13].…”
Section: Introductionmentioning
confidence: 99%